Theoretical study on the hydrogen-bond network and proton switch in ionic mixed clusters - Bing, Dan (2011)
Microsolvation structures of a proton have attracted much interest with respect to the mobility of the proton in the protic solvents. For multi-components systems, the preference of the protonated site has been the subject of extensive studies. In this work, comprehensive analysis on the structure and proton switch in protonated mixed clusters was investigated by theoretical study.